Formação continuada: vivências de professoras alfabetizadoras - Micossi, Milena Marques (2018)
The present research aims at investigating how teachers’ continuing professional development is able to bring about reflection and contribute to the change of literacy teachers’ practices in municipal schools in the city of São Paulo. The development policy within this context is guided by the training suppositions of the Pacto Nacional pela Alfabetização na Idade Certa – PNAIC (National Pact for Literacy at the Right Age). To look into how continuing professional development can contribute to the change of teachers’ activity, the study proposes the analysis of aspects of the training route which may promote reflection and eventual change. It also investigates the action of the former as a mediator in the process of reconstructing and resignifying literacy teachers’ methods, as well as identifies whether there were changes in practice through continuing professional development offered and measured by the suppositions of PNAIC. The theoretical background deployed is composed by Freitas (2007), Placco and Souza (2015), Larrosa (2002), Almeida (2002) and Tardif (2014). The study was conducted at a municipal school of basic education in the region of São Mateus, East Zone of São Paulo. The subjects of the research are five literacy teachers who took part in the 2016’s continuing professional development program. The methodology is qualitative, with the objective of studying the contingencies of the subjects under actual working conditions. Data was collected through a questionnaire and individual and collective interviews, always semi-structured. The analysis of the data has revealed that continuing professional development will likely promote change of practices as long as the professional and formative trajectory of the teachers is taken as a starting point for the reflections, being teaching activity itself the object of study and investigation in the face of the proposition of a formative itinerary which favors meaningful experiences that affect the former and leads to looking for new pedagogical practices. For this purpose, the study has also confirmed that the development must establish dialogical processes which emphasize an active listening and an attentive look from the former towards the groups of teachers, breaking with the conceptual and pragmatic deconstruction discourse to promote the pragmatic resignification mediated by teachers’ trajectory discourse. The research has also testified that the practice as the object of study has fostered its approximation to the theoretical basis, which aroused, besides legitimating literacy teachers’ work, changes of teaching activity in the literacy period